التاثيرات البيئية للمنطقة الصناعية في المدن (Journal of Planner and Development, 2011)
ABSTRACT Studying the positive and negative effects resulted from the industrial projects and laying down the comprehensive planning bases to the urban development projects which insure retaining the social, economic and environmental development, taking in to consternation the time factor within the planning process which is considered the most important factor that determine the extent of the efficient selection to the site and not interpenetrate in the industrial activities and efficiency and calculating its future expansions away from the residential areas. It is more favorable to plan the industrial areas of apparent pollution outside the bounds of the basic plan to limit the negative effects on the environment and providing the modern technology and the necessary techniques to treat the harmful outputs and providing a control station to the pollutions in every industrial area which would limit the appearance of the environment problems which represent the most important outcomes of the developing process and consequently determining the well being of the people of that concerned area with the development process